2012
DOI: 10.1093/carcin/bgs104
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of MYC for transformation of human cells by HPV16 E6E7 and oncogenic HRAS

Abstract: Human papillomaviruses (HPVs) are the primary causal agents for development of cervical cancer, and deregulated expression of two viral oncogenes E6 and E7 is considered to contribute to disease initiation. Recently, we have demonstrated that transduction of oncogenic HRAS (HRAS(G12V)) and MYC together with HPV16 E6E7 is sufficient for tumorigenic transformation of normal human cervical keratinocytes (HCKs). Here, we show that transduction of HRAS(G12V) on the background of E6E7 expression causes accumulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…However, another study found that c‐Myc overacetylation at K323 may reduce its stability . c‐Myc plays a critical role for transformation of human cells by HPV E6 and E7 . c‐Myc interacts with and forms a specific complex with high‐risk type HPV E7 that augmented c‐Myc transactivation activity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study found that c‐Myc overacetylation at K323 may reduce its stability . c‐Myc plays a critical role for transformation of human cells by HPV E6 and E7 . c‐Myc interacts with and forms a specific complex with high‐risk type HPV E7 that augmented c‐Myc transactivation activity .…”
Section: Discussionmentioning
confidence: 99%
“…53 c-Myc plays a critical role for transformation of human cells by HPV E6 and E7. 72,73 c-Myc interacts with and forms a specific complex with high-risk type HPV E7 that augmented c-Myc transactivation activity. 74 The expression of c-Myc correlated to HR-HPV (including HPV-16 and HPV-18)-infected epithelium compared with HR-HPVnegative epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…However, E6 and E7 together are not sufficient, requiring introduction of another cancer risk factor for tumor formation. For example, oncogene Ras has been shown to cause cancer together with E6 and E7 . Deletion of tumor suppressor gene RXRα and expression of E6 and E7 together have also been shown to cause malignant lesions of cervical tissue .…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that transduction of oncogenic HRAS (HRAS G12V ) and MYC together with HPV16 E6E7 is sufficient for highly tumorigenic transformation of primary human cervical keratinocytes (HCKs) . More recently, we found HRAS G12V and HPV16 E6E7 is sufficient for tumorigenic transformation of HCKs . Having taken advantage of this system, we found the PDZ domain‐binding motif plays an important role in tumorigenic transformation of primary HCKs, and further investigated which PDZ domain‐containing target(s) are critical for HPV‐induced cervical carcinogenesis.…”
mentioning
confidence: 99%